Multimedia courseware for children - Yunus, Yasmin; Ayu, Media Anugerah (IIUM Press, 2011)
Multimedia Courseware for children was proposed with the main aim is to make the children mainly age between 5-10 years old good in general knowledge. It also will encourage them to learn and think because at the end of the product there will be quiz to test their understanding on animals. The main objective producing this product is to make children more interesting in learning something. All elements in this product will be conducted in English language. So it will be easier to all the children regardless their origin.